2008
DOI: 10.1093/carcin/bgn246
|View full text |Cite
|
Sign up to set email alerts
|

Aldose reductase deficiency in mice prevents azoxymethane-induced colonic preneoplastic aberrant crypt foci formation

Abstract: Aldose reductase (AR; EC 1.1.1.21), an nicotinamide adenine dinucleotide phosphate-dependent aldo-keto reductase, has been shown to be involved in oxidative stress signaling initiated by inflammatory cytokines, chemokines and growth factors. Recently, we have shown that inhibition of this enzyme prevents the growth of colon cancer cells in vitro as well as in nude mice xenografts. Herein, we investigated the mediation of AR in the formation of colonic preneoplastic aberrant crypt foci (ACF) using azoxymethane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 41 publications
4
51
0
3
Order By: Relevance
“…Small interfering RNA-mediated knock down of AKR1B10 in cancer cells resulted in 50% decrease of cell growth rate and in decreased expression of preneoplastic marker proteins such as cyclin D1 and beta-catenin in mice colons [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Small interfering RNA-mediated knock down of AKR1B10 in cancer cells resulted in 50% decrease of cell growth rate and in decreased expression of preneoplastic marker proteins such as cyclin D1 and beta-catenin in mice colons [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Our recent studies in human colon cancer cells, human lens epithelial cells, vascular endothelial cells and vascular smooth muscle cells suggest that the polyol pathway enzyme, aldose reductase (AR), a member of aldo–keto reductase super family, is a regulator of ROS signals induced by growth factors, cytokines, chemokines, lipo-polysaccharide and high glucose (HG) [1219]. Overexpression of AR has been shown in the tissues of diabetic and obese subjects [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Most remarkably, in the nude mouse xenograft model, we have shown that inhibition of AR by AR siRNA as well as by the AR inhibitor fidarestat completely prevented progression of tumor growth of human colon cancer cells (SW480 and HT29) implanted in nude mice subcutaneously (21). Furthermore, recent results with azoxymethane model in male BALB/c mice showed that inhibition of AR by pharmacological inhibitor of AR as well as AR gene knockout in mice significantly prevented aberrant crypt foci formation and azoxymethane-induced expression of inflammatory markers, inducible nitric oxide synthase and cyclooxygenase-2 (Cox-2) and preneoplastic marker proteins, cyclin D1 and ␤-catenin and activation of NF-B in mouse colons (25). However, the involvement of AR in the hypoxia-mediated carcinogenesis is unknown.…”
mentioning
confidence: 99%